Assessing interpersonal skills—A comparison of trainee therapists' and students' interpersonal skills assessed with two established assessments for interpersonal skills. (21st June 2020) - Wolfer, Christine; Vîslă, Andreea; Held, Judith; Hilpert, Peter; Flückiger, Christoph
Abstract: Therapist differences in psychotherapy outcomes have been consistently found. Therefore, therapists' characteristics such as interpersonal skills are of particular interest. Two assessments of interpersonal skills for the selection of trainees have recently been developed. To extend current knowledge, this study compares trainee therapist's and psychology student's interpersonal skills in both assessments simultaneously and also investigates the potential influence of clinical experience and age on interpersonal skills. Furthermore, the psychometric properties of these assessments are examined. A total of 19 trainee therapists and 17 undergraduate students ( N = 36) participated in both assessments and provided information on their prior clinical experience. Trainee therapists had significantly better interpersonal skills than the students in both assessments. However, different indicators of clinical experience (e.g., years in practice, patients treated, and supervision) did not influence their performance in either assessment. The good psychometric properties of both assessments could be replicated. Conceptual and practical considerations on the assessment of interpersonal skills are discussed.